Soil drenching of paclobutrazol: An efficient way to improve quinoa performance under salinity. Issue 2 (2nd October 2018) - Waqas, Muhammad; Yaning, Chen; Iqbal, Hassan; Shareef, Muhammad; ur Rehman, Hafeez; Iqbal, Shahid; Mahmood, Sajid
Abstract : Salinity extent and severity is rising because of poor management practices on agricultural lands, possibility lies to grow salt‐tolerant crops with better management techniques. Therefore, a highly nutritive salt‐tolerant crop quinoa with immense potential to contribute for future food security was selected for this investigation. Soil drenching of paclobutrazol (PBZ; 20 mg l −1 ) was used to understand the ionic relations, gaseous exchange characteristics, oxidative defense system and yield under saline conditions (400 mM NaCl) including normal (0 mM NaCl) and no PBZ (0 mg l −1 ) as controls. The results revealed that salinity stress reduced the growth and yield of quinoa through perturbing ionic homeostasis with the consequences of overproduction of reactive oxygen species (ROS), oxidative damages and reduced photosynthesis. PBZ improved the quinoa performance through regulation of ionic homeostasis by decreasing Na +, Cl −, while improving K +, Mg 2+ and Ca 2+ concentration. It also enhanced the antioxidative system including ascorbic acid, phenylalanine ammonia‐lyase, polyphenol oxidase and glutathione peroxidase, which scavenged the ROS (H2 O2 and O2 ‐ ) and lowered the oxidative damages (malondialdehyde level) under salinity in roots and more specifically in leaf tissues. The photosynthetic rate and stomatal conductance consequently improved (16 and 21%, respectively) in salt‐stressed quinoa PBZ‐treated compared to the non‐treated ones and contributed to the improvement of panicle length (33%), 100‐grain weight (8%) and grain yield (38%). Therefore, PBZ can be opted as a shotgun approach to improve quinoa performance and other crops under high saline conditions.